Synthesis of polypyrrole/cellulose nanocrystals disks for removal of pyocyanin metabolite biomarker released by Pseudomonas aeruginosa. - Waleed A El-Said; Ziya A Khan; Deia A El-Hady; Wael Alshitari; Mostafa Kamal Masud; Yusuke Yamauchi (PLoS ONE)
Pseudomonas aeruginosa is a high-risk pathogen associated with several human diseases. Pyocyanin (PYO), a redox-active secondary metabolite produced by P. aeruginosa, plays a critical role in its survival and pathogenicity, exhibiting both antibacterial and toxic properties. Recent studies have shown that reducing PYO production can inhibit the growth of P. aeruginosa. Here, we report the extraction of cellulose nanocrystals from rice husk for the fabrication of cellulose nanocrystal/polypyrrole (PPy/cellulose) composite disks. This nanocomposite disk acts as a simple, highly efficient, and cost-effective adsorbent for removing PYO metabolites from contaminated water samples. The chemical and morphological features of the PPy/cellulose composites are investigated using various techniques. Solid-phase extraction is employed to remove PYO, with treatment conditions optimized for maximum efficiency. Both two-parameter and three-parameter models are used to analyze the equilibrium data for PYO removal. The optimal adsorbent dose is found to be 20 mg at 303 K for 35 minutes. The PPy/cellulose disk reaches maximum adsorption, removing over 93% of 10 ppm PYO. This approach presents a novel and effective strategy for mitigating the harmful effects of PYO, with potential applications in treating P. aeruginosa infections and recycling PYO for antimicrobial use.